THE DEVELOPMENT OF THE INTEGRATED SOCIAL SERVICES SYSTEM IN ARMENIA - Vardanyan, Yevgine (Journal of Sociology: Bulletin of Yerevan University, 2024)
There are many approaches in the literature that describe the integrated social services concept and analyze the processes, mechanisms and the purposes of integrating social and/or other multispectral services. The models of integration are also the object of some analysis, but still there is a lack of description of the services’ integration models, and a necessity in clearly defining and describing them. The article comes to fulfill this gap, and also to analyze the experience of the Republic of Armenia in integrating social services. The reform lasted almost 10 years, and still the country struggles the difficulties in ensuring the effectiveness and accessibility of those services. Hence, the article is aimed at revealing the main problems and omissions that have occurred and still exist within the frame of the reform. For achieving the main goals proposed for the article, the following research methods have been used: documentary analysis, focus group discussions, and participant observation. The main results of the research make obvious that Armenia passed two main phases for integrating social services. During the first phase the country was able to ensure only co-location of the state agencies that were responsible for provision of social services, locating them in one building with one reception, but no more. For fulfilling the reform, the second phase of integration was launched in 2021, and during that phase the integration was performed with the usage of the principles of structural and functional changes as a model of integrating social service. Meanwhile, for making the whole system work, Armenia needs to go forward and achieve also integration of the procedures, protocols and databases of the services, as well as ensuring the change in the cultural and organizational norms of the newly established system, enhancing cooperation and partnership between the staff of integrated services. This will certify the implementation of another model of integrating social services that is full integration model.